Handling and Prevention of Bullying of Children in Schools : Study at SMA Negeri 1 Tembilahan in 2024 - Gumilang, M. Aryo; Sobri, Sobri; Munir, Abdul (Teunuleh Publisher, 2025)
This study aims to analyze strategies for handling and preventing bullying in the school environment, with a case study at SMA Negeri 1 Tembilahan. Bullying is still a serious problem in the world of education, not only in the form of physical violence, but also verbal, social, and psychological. The impact not only disrupts the student learning process, but also causes long-term psychological disorders. This study uses a qualitative approach with a case study method. Data was collected through observations, in-depth interviews, and documentation involving teachers, students, and the school. The results of the study show that the handling of bullying at SMA Negeri 1 Tembilahan is still reactive, namely actions are only taken after the incident occurs. Schools do not yet have a structured prevention system, including clear reporting procedures, teacher training, and active parental involvement. In addition, the lack of supervision in the school environment and the weak socialization of anti-bullying values also worsened the situation. Despite the efforts of BK teachers and homeroom teachers in handling cases that arise, the approach taken has not touched the root of the problem comprehensively. This study recommends the importance of implementing prevention strategies based on situational approaches, strengthening character education, and cross-stakeholder collaboration to create a safe and bullying-free learning environment.